Life history of Eretmocerus mundus, a parasitoid of Bemisia tabaci, on tomato and sweet pepper - Urbaneja, Alberto; Sánchez, E.; Stansly, Philip A. (2017)
Eretmocerus mundus is native to the Mediterranean region where it is often observed to enter greenhouses to parasitize B. tabaci on fruiting vegetables and other host crops. Fecundity on tomato and pepper was evaluated by placing newly emerged pairs (n = 15) of E. mundus on leaf discs infested with second instar B. tabaci, the preferred stage, maintained at 25°C and changed daily until death of the female. All whitefly nymphs were observed for host feeding and inverted to count parasitoid eggs. Adult longevity was estimated at 7.3±0.8 d on tomato and 10.1±1.0 d on sweet pepper. Fecundity (number of hosts parasitized) was estimated 147.8±12.6 per female on tomato and 171.1±21.5 on pepper. Incidence of host feeding (number of hosts killed) was significantly greater on sweet pepper than on tomato, 15.6±1.9 vs. 10.4±1.3 nymphs per female, respectively. No significant differences were detected in the duration of life stages between sweet pepper and tomato. Preimaginal survivorship in clip cages was estimated at 69.5±11.9% on tomato and 76.6±10.5% on sweet pepper, with no statistical differences. Net reproductive rate (R o) was estimated at 63.8±8.2 and 51.0±4.4 on tomato and sweet pepper respectively. Generation time (T) was significantly greater on sweet pepper (19.3±0.5) than on tomato (17.9±0.4), but the estimate of intrinsic rate of increase (r m) was not statistically different at 0.216±0.005 and 0.219±0.004 respectively. These values are well above those reported for B. tabaci on any crop, indicating the potential of E. mundus to control this pest on solanaceous crops in the greenhouse. © 2006 IOBC.